Experimental Study of Concrete Subjected to Explosive Loading - Rekucki, R.; Kruszka, L. (Проблемы прочности, 2002)
The main subject of this paper was to demonstrate the response of structural concrete to different imposed strain rates. Attention is focused on the strain rate about 10^-2 s^-1, where some technical difficulties are experienced when an exact determination of mechanical properties for quasi-brittle materials is attempted. The design of a measurement system, which realizes computer acquisition, analysis and graphics pictures viewing of date, is also presented. Выполненные экспериментальные исследования свидетельствуют о влиянии различных скоростей деформирования на прочность конструкционного бетона. Особое внимание уделено скорости деформирования 10^-2 с^-1 для которой проблематично точно определить механические характеристики квазихрупких материалов. Приведена новая конструкция системы измерения, в которой реализуются компьютеризованное получение, обработка и графическое представление экспериментальных данных. Проведені експериментальні дослідження свідчать про вплив різної швидкості деформування на міцність конструкційного бетону. Особлива увага зосереджена на швидкості деформування 10^-2 c^-1 , для якої проблематично точно визначити механічні характеристики квазікрихких матеріалів. Наведено нову конструкцію системи вимірювання, в якій реалізуються комп’ютеризоване одержання експериментальних даних, їхня обробка та графічне зображення.